2006
DOI: 10.1086/506350
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Newly Identified Respiratory Viruses with Lower Respiratory Tract Infections in Korean Children, 2000–2005

Abstract: This study describes the features of LRTIs associated with newly identified viruses in children, compared with those associated with known viruses. Additional investigations are required to define the role of HBoV in LRTI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

57
289
23
17

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(386 citation statements)
references
References 39 publications
57
289
23
17
Order By: Relevance
“…However, our results show that LRTI associated with viral co-infection does not result in a higher incidence of severe syndromes compared to infection with HRV alone. Other groups have reported similar results (Williams et al 2004, Choi et al 2006, Calvo et al 2007, Louie et al 2009). …”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…However, our results show that LRTI associated with viral co-infection does not result in a higher incidence of severe syndromes compared to infection with HRV alone. Other groups have reported similar results (Williams et al 2004, Choi et al 2006, Calvo et al 2007, Louie et al 2009). …”
Section: Discussionsupporting
confidence: 68%
“…Due to advances in nucleic acid amplification, we can now detect HRV and determine when HRV is the causative agent of lower respiratory tract illness (LRTI) (Choi et al 2006, Miller et al 2007, Gerna et al 2009, Louie et al 2009). HRV is frequently detected in children diagnosed with bronchiolitis and pneumonia (Manoha et al 2007, Miller et al 2007, Louie et al 2009).…”
mentioning
confidence: 99%
“…1). Previous studies detected HBoV mainly in children less than 5 years old and mostly in infants less than 2 years old (Choi et al, 2006;Kaplan et al, 2006;Kesebir et al, 2006;Kleines et al, 2007;Brieu et al, 2008;Canducci et al, 2008;Cilla et al, 2008). However, a recent report (Guido et al, 2011) and the present work confirm that HBoV1 is also a frequent virus in adults with respiratory disease.…”
Section: Resultscontrasting
confidence: 46%
“…In patients, diagnosed with ARI the most frequently detected virus was HRV -33 (16.75%) ( Table 3). (8)(9)(10)(11)(12). Coinfections in this study were identified in a relatively small percentage of cases (3.15%).…”
Section: Clinical Characteristicsmentioning
confidence: 54%